A General Synthesis of Porous Carbon Nitride Films with Tunable Surface Area and Photophysical Properties. (12th December 2017) - Peng, Guiming; Xing, Lidan; Barrio, Jesús; Volokh, Michael; Shalom, Menny
Abstract: Graphitic carbon nitride (g‐CN) has emerged as a promising material for energy‐related applications. However, exploitation of g‐CN in practical devices is still limited owing to difficulties in fabricating g‐CN films with adjustable properties and high surface area. A general and simple pathway is reported to grow highly porous and large‐scale g‐CN films with controllable chemical and photophysical properties on various substrates using the doctor blade technique. The growth of g‐CN films, ascribed to the formation of a supramolecular paste, comprises g‐CN monomers in ethylene glycol, which can be cast on different substrates. The g‐CN composition, porosity, and optical properties can be tuned by the design of the supramolecular paste, which upon calcination results in a continuous porous g‐CN network. The strength of the porous structure is demonstrated by high electrochemically active surface area, excellent dye adsorption and photoelectrochemical and photodegradation properties.